Problematika Pembelajaran Pendidikan Agama Islam bagi Siswa Berkebutuhan Khusus pada Kelas Inklusi di SMP Negeri 7 Samarinda - Kartika, Ayu; Husin, M.Said; Rahmawati, Indriana (Sultan Idris Journal of Psychology and Education, 2023)
The aim of this research is to find out problems and solutions in implementing PAI learning for ABK in inclusion classes at SMP Negeri 7 Samarinda. The research method used is descriptive qualitative research. Data collection techniques are observation, interviews and documentation. Data analysis techniques are data reduction, data presentation, and conclusions. The results of this research are problems in implementing PAI learning for ABK in inclusion classes at SMP Negeri 7 Samarinda, including the absence of a special curriculum for ABK students. there is no expert staff (GPK) who graduated from PLB. Inadequate facilities and infrastructure, easily changing mood disorders & reflex movements of autistic students. Communication breakdown. The difficulty of slow learner students in understanding the material. Solutions to overcome problems in implementing PAI learning for ABK in inclusion classes at SMP Negeri 7 Samarinda include evaluation standards for ABK students which are different from normal students and a personal approach. Collaboration between the school, parents and the UPTD.PLDPI institution as well as participating in training. Make use of the available facilities. Use of the method (ABA) for autistic students, use of non-verbal communication and classroom management for deaf students. Using the drill method for slow learners.